IgD shapes the pre-immune naïve B cell compartment in humans - Dirks, Johannes; Andres, Oliver; Paul, Luisa; Manukjan, Georgi; Schulze, Harald; Morbach, Henner (Frontiers in Immunology, 2023)
B cell maturation and immunoglobulin (Ig) repertoire selection are governed by expression of a functional B cell receptor (BCR). Naïve B cells co-express their BCR as IgM and IgD isotype, however, the role of the additionally expressed IgD on naïve B cells is not known. Here we assessed the impact of IgD on naïve B cell maturation and Ig repertoire selection in 8 individuals from 3 different families with heterozygous loss-of-function or loss-of expression mutations in IGHD. Although naïve B cells from these individuals expressed IgM on their surface, the IGHD variant in heterozygous state entailed a chimeric situation by allelic exclusion with almost half of the naïve B cell population lacking surface IgD expression. Flow cytometric analyses revealed a distinct phenotype of IgD-negative naïve B cells with decreased expression of CD19, CD20 and CD21 as well as lower BAFF-R and integrin-β7 expression. IgD-negative B cells were less responsive in vitro after engaging the IgM-BCR, TLR7/9 or CD40 pathway. Additionally, a selective disadvantage of IgD-negative B cells within the T2 transitional and mature naïve B cell compartment as well as reduced frequencies of IgMlo/- B cells within the mature naïve B cell compartment lacking IgD were evident. RNA-Ig-seq of bulk sorted B cell populations showed an altered selection of distinct VH segments in the IgD-negative mature naïve B cell population. We conclude that IgD expression on human naïve B cells is redundant for generation of naïve B cell in general, but further shapes the naive B cell compartment starting from T2 transitional B cells. Our observations suggest an unexpected role of IgD expression to be critical for selection of distinct Ig VH segments into the pre-immune Ig repertoire and for the survival of IgMlo/- naïve B cells known to be enriched in poly-/autoreactive B cell clones.